Kilas-Balik Wabah di Indonesia: Mengurai Kembali Pandemi COVID-19 Melalui Peristiwa Flu Spanyol 1918-1920 - Muhammad Khodafi; Wildayati Wildayati; Rizki Endi Septiyani (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This paper aims to determine (1) the events of the Spanish Influenza 1918-1920 pandemic in Indonesia, (2) the COVID-19 pandemic in Indonesia, and (3) a map of the COVID-19 pandemic through the Spanish Influenza1918-1920 in Indonesia. This research uses qualitative methods through literature study techniques. The data obtained were analyzed using the phenomenological theory of Alfert Schurtz. The results of this study indicate if (1) the Spanish Influenza1918 in Indonesia can be categorized through the history, impact, and efforts to overcome the pandemic in Indonesia, (2) the COVID-19 pandemic in Indonesia can be mapped into three parts (discussion) similar to the Spanish Influenza 1918 in Indonesia, and (3) a map of the COVID-19 pandemic through the Spanish Influenza 1918 in Indonesia. Overall these two pandemic events can be correlated as historical repetitions, that is, between the past and the present. This research is expected to find continuity as a historical fact as well as learning material in the future.